Analisis Faktor-Faktor yang Memengaruhi Luas Pengungkapan Sukarela (Voluntary Disclosure) dalam Laporan Tahunan Perusahaan - Mia Agustina Puspasari; Ayang Suchita Maladika Rahmah (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2018)
This research aimed to figured out the effect of company size, company age, leverage, profitability and liquidity towards voluntary disclosure. The data collection method used in this study was documentation by getting the data of published company annual report. The population used in this study was consumer goods industry sector of manufacturing company listed in Indonesia Stock Exchange along period of 2012-2016. The sample was taken using purposive sampling method which generated 95 samples of year 2012-2016. Moreover, the data analysis technique used was descriptive statistics. Also, this study used classical assumption test: normality test, multikolinearity test, autocorrelation test and heteroskedastisitas test. While for hypothesis testing using multiple linear regression analysis. The result of t-test (partially) showed that the two independent variables which consisted of company size and company age significantly effect the voluntary disclosure. Meanwhile, the other three variables (leverage, profitability and liquidity) had no significant effect towards the voluntary disclosure. Simultaneously, company size, company age, leverage, profitability and liquidity significantly effect the voluntary disclosure. This study was conducted only in one sector of manufacturing company.